2014
DOI: 10.5194/nhessd-2-3465-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perception of flood and landslide risk in Italy: a preliminary analysis

Abstract: Abstract. Inundations and landslides are widespread phenomena in Italy, where they cause severe damage and pose a threat to the population. Little is known on the perception of the population of landslides and floods. This is surprising, as an accurate perception is important for the successful implementation of many risk reduction or adaptation strategies. In an attempt to fill this gap, we have conducted two national surveys to measure the perception of landslide and flood risk of the population of Italy. Th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…However, previous studies on disaster-risk management have primarily focused on single types of disasters such as earthquakes, floods, or landslides [ 11 , 12 , 13 ]; there has been little attention paid to situations where the risk of multiple disasters coexists. Furthermore, the research areas were mainly in developed countries such as the USA and in Europe [ 14 , 15 , 16 ], with relatively few in developing countries or in Asia.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies on disaster-risk management have primarily focused on single types of disasters such as earthquakes, floods, or landslides [ 11 , 12 , 13 ]; there has been little attention paid to situations where the risk of multiple disasters coexists. Furthermore, the research areas were mainly in developed countries such as the USA and in Europe [ 14 , 15 , 16 ], with relatively few in developing countries or in Asia.…”
Section: Introductionmentioning
confidence: 99%
“…This research explored the flood RP of residents in small rural areas, mainly in Alpine zones exposed to hydrogeological risk in the North of Italy (Miceli et al, 2008; Scolobig, DeMarchi, & Borga, 2012), and in larger urban areas (Mysiak et al, 2013) with a long track record of severe floods. Two national surveys (Salvati et al, 2014) showed a general tendency to underestimate flood risk, highlighting an evident gap between the actual risk posed by landslides and floods to the local population and their perception of the dangerousness of hydrogeological events.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent decades, a number of rainfall events have caused widespread landslides and inundations in Italy, resulting in serious social and economic damage (Wasowski, 1998;Alpert et al, 2002;Crosta and Frattini, 2003;D'Amato Avanzi et al, 2004;2012;Luino, 2005;Giannecchini, 2006;Del Ventisette et al, 2012;Salvati et al, 2014). In the same period, the Nat.…”
Section: Introductionmentioning
confidence: 99%